Os tipos de climas anuais no Brasil : uma aplicação da classificação de Köppen de 1961 a 2015 - Vincent Dubreuil; Karime Pechutti Fante; Olivier Planchon; João Lima Sant'anna Neto (Confins)
This article proposes to use the Köppen classification to define "Annual Climate Types" (ACT) for a set of 208 stations, representative of the climatic diversity of Brazil. The average monthly temperature and precipitation data for the period 1961-2015 allow to establish the frequency of ACTs for each station. The statistical and cartographic treatment of this information makes it possible to define the limits of the climates of Brazil: here we apply the concepts of "strong nuclei", defined as the regions where the ACT are systematically or mostly the same, and "transition areas ", i.e. regions where there is a great diversity of ACT. This approach allows us to propose a detailed study of the transitions between the tropical climates types (mainly Aw, Am and Af) and those of the south, subtropical and temperate (Cwa and Cfa in particular) and discuss these climatic limits.